Engaging customers in the restaurante sector - Itani, O. S.; Kassar, A.-N.; Loureiro, S. M. C. (Conference book proceedings of the 3rd international Conference on Organization and Management (ICOM), 2017)
In today’s market, customers are not only consuming the market offerings of the firms, but also marketing these offerings indirectly through different engagement behaviors. Evidence suggest that customer engagement drives key business outcomes. In turn, more attention is given to customer engagement from business practitioners and researchers. This paper examines the factors driving customers to engage with restaurants. The authors built on the theory of engagement and marketing relationship literature to propose that customer perceived value and relationship quality are antecedents of customer engagement. Moreover, the authors test a mediated relationship between customer perceived value and customer engagement through relationship quality. Additionally, customer value consciousness is incorporated to the model as a boundary condition of the positive effects of customer perceived value on customer engagement and relationship quality. Results of the hypothesized relationships are provided. At the end, discussion of theoretical and managerial implications is found.